Study of Nutrition Content Food Drop in Deer in PT. Gunung Madu Plantations - Jumayanti Boru Hombing; Bainah Sari Dewi; Syahrio Tantalo; Sugeng Prayitno Harianto (Jurnal Sylva Lestari, 2018)
Increasing the number of individual deer in captivity indicates an increase in the deer population. One of the factors affecting the increase in the deer population is a drop in the quality of feed and nutritional value adequate for deer. Therefore it is necessary to investigate the type of feed and feed nutrient content in captive deer drop in PT Gunung Madu Plantations (GMP). Nutrient content of feed drop in deer obtained through the proximate analysis by taking a sample of 100 grams per sample feed. This type of feed given drop in manager consists of the main feed forage consisting of grass and leaves, in the form of rice bran concentrate feed, and feed the tubers were given every month. Based on proximate analysis that has been made known that the feed drop-in provided by the organizer captivity contains good nutrition, as seen in the high water content, extract ingredients without nitrogen (BETN) high, protein and fibers that do not differ greatly in value and fat content is not excessive. Keywords: Drop in Feed Nutrition, Feeding Deer, Captive Deer PT. GMP